Emotional Tension as a Frame for Argumentation and Decision-Making: Vegetarian vs. Omnivorous Diets - Jiménez-Aleixandre, María Pilar; Brocos, Pablo (Frontiers in Psychology, 2021)
Argumentative discourse has a complexity that is not entirely captured by purely structural analyses. In arguments about socio-scientific issues (SSI), a range of dimensions, besides scientific knowledge, including values, ethical concerns, cultural habits, or emotions, are mobilized. The relationship between argumentation and emotions is now drawing attention of researchers. Our focus is on the dynamic interactions among emotions and scientific evidence. We draw from Plantin, who proposed that emotions are mobilized as argumentative resources alongside knowledge. The goal of our study is to examine in which ways emotional tension frames the construction of arguments about vegetarian vs. omnivorous diets (ODs) with a group of four preservice teachers. The results suggest that the interactions between the group emotional tension and the evaluation of evidence drive a change toward a decision that would be emotionally acceptable for all participants. Participants attended to the epistemic dimension, weighing evidence, and values about the choices, but the emotional framing took priority. We suggest that the analysis of this emotive framing may be a fruitful approach for sophisticated studies of argumentation beyond structural issues.